2021
DOI: 10.1093/ibd/izab038
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis and Clinical Management of Stricturing Crohn Disease

Abstract: Stricturing of the gastrointestinal tract is a common complication in Crohn disease and is a significant cause of morbidity and mortality among this population. The inflammatory process initiates fibrosis, leading to aberrant wound healing and excess deposition of extracellular matrix proteins. Our understanding of this process has grown and encompasses cellular mechanisms, epigenetic modifications, and inherent genetic predisposition toward fibrosis. Although medications can improve inflammation, there is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 118 publications
0
5
0
1
Order By: Relevance
“… 44 However, the underlying mechanisms through which NOD2 drives fibrosis formation remain elusive. 6 Nayar et al 45 first unveiled how NOD2 deficiencies predisposed CD patients to develop a stricturing phenotype [ Figure 2(e) ]. They defined a unique activated fibroblast population characterized by CD14 and PDGFRA expression via single-cell RNA sequencing of inflamed ileum from patients with CD.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“… 44 However, the underlying mechanisms through which NOD2 drives fibrosis formation remain elusive. 6 Nayar et al 45 first unveiled how NOD2 deficiencies predisposed CD patients to develop a stricturing phenotype [ Figure 2(e) ]. They defined a unique activated fibroblast population characterized by CD14 and PDGFRA expression via single-cell RNA sequencing of inflamed ileum from patients with CD.…”
Section: Search Strategymentioning
confidence: 99%
“… 5 However, they are not ideal due to a high rate of postoperative recurrence and complications. 6 To date, there are still no licensed antifibrotic agents, 7 partly due to the poor understanding of the mechanisms of initiation and propagation of intestinal fibrosis. Specific predictors that are capable of identifying CD patients at a high risk of developing strictures are also lacking, which may account for the lack of timely treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Хронічне запалення, численні виразки та пошкодження стінок кишечника можуть викликати неконтрольоване відкладання позаклітинного матриксу (ПКМ) та бути причиною розвитку фібротичних змін [4,5], оскільки основними компонентами ПКМ є фібронектин, колагени, ламініни та протеоглікани [6,7,18]. Тому основні ускладнення при ХК, що можуть вимагати хірургічного втручання, включають утворення фіброзних стриктур, нориць, зниження всмоктувальної функції, ризик розвитку раку.…”
Section: вступunclassified
“…Crohn's disease (CD) is characterized by chronic and relapsing intestinal inflammation, and hypertrophy of mesenteric adipose tissue (MAT) enveloping the lesions in the intestine 1–3 . The crosstalk between MAT and the intestine affects the progression of CD 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Crohn's disease (CD) is characterized by chronic and relapsing intestinal inflammation, and hypertrophy of mesenteric adipose tissue (MAT) enveloping the lesions in the intestine. 1 , 2 , 3 The crosstalk between MAT and the intestine affects the progression of CD. 4 Studies have shown that the MAT in CD exhibits endocrine and metabolic dysfunction, 5 as well as poor differentiation, 6 and little is known about the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%